Assessment of biomedical and pharmacological activities of sea anemones Stichodactyla mertensii and Stichodactyla gigantea from Gulf of Mannar Biosphere Reserve, southeast coast of India - Thangaraj,S (2012)
Cnidarians comprise an old and diverse animal phylum, and possess a wide variety of biologically active substances. Sea anemones contain a diversity of interesting biologically active compounds including some potent toxins. In the present work, the sea anemones Stichodactyla mertensii and Stichodactyla gigantea, collected from the Mandapam coast, are characterized biomedically and pharmacologically. The crude protein was obtained by using methanol and aqueous extracts. The respective protein contents of S. mertensii and S. gigantea were found to be 2.10 µg/mL and 1.87 µg/mL. The methanol and aqueous extracts of S. mertensii and S. gigantea yielded six and nine bands by SDS-PAGE on 12% gel. In the hemolytic assay, both extracts exhibited hemolytic effect on chicken, goat, cow and human erythrocytes ('A', 'B' and 'O'). The neurotoxic effects of these crude extracts were determined in vivo using the sea shore crab Ocypode macrocera and mortality was observed. The mouse bioassay for lethality was performed on male albino mice. The crude extract of S. mertensii showed higher lethality (58 seconds at 1 mL-dose) than that of S. gigantea (2 minutes and 10 seconds at 0.75 mL-dose). The analgesic activity test was also carried out on albino mice by Eddy's hot plate and tail-flick methods. The extracts showed moderate analgesic effect by both hot-plate and tail-flick methods. These characteristics emphasize the need for the isolation and molecular characterization of new active toxins in S. mertensii and S. gigantea.